Breathing Hemispheres (skies 66.1100° N, 18.5300° W + 32.0569° S, 115.7439° E) ... - Duxbury, Lesley (RMIT University, 2024)
BACKGROUND Aristotle made connections between the body and the atmosphere, comparing our breathing in and breathing out to atmospheric exhalations. Lesley Duxbury and Paul Uhlmann have long been fascinated by the sky and its phenomena. In this first collaborative project they expanded their concerns to include the air we breathe. According to David Suzuki, "Air is a physical substance; it embraces us so intimately that we cannot say where we leave off and air begins". 2 remote locations, Fremantle and N Iceland, provided opportunities for pure contemplation of the sky and relationship to life through breathing and absorption of the atmosphere. Friedrich's painting 'Two men gazing at the moon' depicting two men as Rückenfiguren was the catalyst for this project. CONTRIBUTION In October 2015 Lesley Duxbury, artist in residence in remote N Iceland, documented the sky at key periods of the day and night corresponding with the same times Paul Uhlmann documented the sky from his home base in remote Fremantle. 2 ...